Analisis Sentimen Konsumen Selama Pandemi Covid-19 di Kota Semarang Menggunakan Tableau - Nugraha, Aryan Eka Prastya; Riyanto, Riyanto; Sari, Inayah Adi; Hadi, Dwi Prastiyo (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
This study aims to analyze consumer sentiment during the pandemic in Semarang City. The data analysis techniques used are: (1) Business Intelligence with data visualization using Tableau and (2) to determine the effect or impact of the results of consumer sentiment, the second analysis uses trend analysis to estimate complex future prediction models. Based on the results that have been carried out in research on consumer sentiment and its impact on the retail business in Semarang City, consumer consumption patterns during the pandemic remain unchanged compared to before the pandemic. The conclusion in this study is the projection of time and expectations for retail businesses during the pandemic, which is an average of 6 months after the pandemic subsides they will return to normal. It also adjusts to the financial and operational capabilities of each retailer.